2007
DOI: 10.1007/s12010-007-9041-7
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of corn stover by soaking in aqueous ammonia at moderate temperatures

Abstract: Soaking in aqueous ammonia at moderate temperatures was investigated as a method of pretreatment for enzymatic hydrolysis as well as simultaneous saccharification and cofermentation (SSCF) of corn stover. The method involves batch treatment of the feedstock with aqueous ammonia (15-30 wt%) at 40-90 degrees C for 6-24 h. The optimum treatment conditions were found to be 15 wt% of NH(3), 60 degrees C, 1:6 of solid-to-liquid ratio, and 12 h of treatment time. The treated corn stover retained 100% glucan and 85% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 12 publications
(12 reference statements)
5
43
1
Order By: Relevance
“…Relatively few studies have reported on application of SAA with lignocellulosic resources, such as corn stover, rice straw, and barley hull [18][19][20]. According to Kim and Lee [17], SAA treatment of corn stover at room temperature and a long treatment period (10-60 days) resulted in removal of 55-74% of the lignin; however, nearly 100% of the glucan and 85% of the xylan were retained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively few studies have reported on application of SAA with lignocellulosic resources, such as corn stover, rice straw, and barley hull [18][19][20]. According to Kim and Lee [17], SAA treatment of corn stover at room temperature and a long treatment period (10-60 days) resulted in removal of 55-74% of the lignin; however, nearly 100% of the glucan and 85% of the xylan were retained.…”
Section: Resultsmentioning
confidence: 99%
“…According to Kim and Lee [17], SAA treatment of corn stover at room temperature and a long treatment period (10-60 days) resulted in removal of 55-74% of the lignin; however, nearly 100% of the glucan and 85% of the xylan were retained. Kim and Lee [18] reported that optimum treatment conditions for SAA of corn stover at moderate temperature were 15% of NH 3 , 60°C, 1:6 of solid-to-liquid ratio, and 12 h treatment time. The treated corn stover retained 100% of glucan and 85% of xylan; however, 62% of lignin was removed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…# A669C) and a solid-to-liquid ratio (w/w) of 1:11. The pretreatment was performed in screw-capped Pyrex media bottles (250 ml) at 60°C (maintained by convection oven) without agitation for 12 h. These conditions were chosen based on the results obtained previously for SAA pretreatment of corn stover [15,16]. The pretreated corn stover was washed with deionized (DI) water using vacuum filter and fluted filter paper (Fisher Cat.…”
Section: Pretreatmentmentioning
confidence: 99%
“…Many softwood pretreatment methods have been studied, including acid hydrolysis (Kumaar et al 2012;Normark et al 2014), wet oxidation (Rana et al 2012;Njoku et al 2012;), steam explosion (Brownell et al 1986;), SO2 pretreatment (Sassner et al 2005), oxygen delignification (Yang and Wyman 2008;Wu et al 2012), catalytic pretreatment (Hakola et al 2010), Organosolv (Pan et al 2007), aqueous ammonia soaking (Kim and Lee 2007;Ko et al 2009), sulfite pretreatment (Zhu et al 2009), green liquor pretreatment (Wu et al 2010), and alkali pretreatment (Salehian et al 2013). These pretreatment methods affect enzymatic hydrolysis of biomass differently and also introduce different degrees of complexity in process technology and chemical cost/recovery.…”
Section: Introductionmentioning
confidence: 99%